Peran Penyuluh Agama dalam Meningkatkan Nilai Religius Masyarakat Pesisir dengan Menggunakan Metode Bimbingan Penyuluhan Islam - Aisya Khomsati; Khaerunnisa Tri Darmaningrum (Al Irsyad : Jurnal Bimbingan Konseling Islam, 2023)
Religious instructors have an important role in increasing the religiosity of coastal communities. Islamic counseling guidance methods can be used to increase understanding of religion and religious behavior in coastal communities. The method used in this research is a qualitative method with a library study approach, namely collecting research data through journals, books or other literature. Several effective methods in increasing the religiosity of coastal communities through Islamic education guidance include using direct lectures and group activities, implementing Islamic religious education in the family, providing guidance and counseling, collaborating with local religious organizations, as well as providing motivation and leading religious activities in the area. public . In carrying it out, religious counselors can also help understand understandings and practices that are not in accordance with Islamic teachings. Collaboration between religious instructors and local religious organizations can support the implementation of Islamic religious education and increase its effectiveness. There are several methods that can be used by religious instructors to make coastal communities at least begin to understand and deepen the religion of Islam. With this, the author hopes that future researchers can develop further regarding the solutions offered to increase the religiosity of coastal communities.